The Correlation Between Students Reading Anxiety and Their Reading Comprehension at the Eighth Grade of SMPN 3 Bukittinggi - Hafiza, Maqsuratun; Syafitri, Widya; Eliza, Eliza; Putri, Hilma Pami (Pusdikra Publishing, 2024)
Theoretically, reading anxiety can affect their reading comprehension. This research is aimed to uncover whether there is a correlation between reading anxiety and their reading comprehension. Empirically, the rationalities of the research are based on the three main rationales. Firstly, The pupils experience anxiety when attempting to understand the English texts, and occasionally they exploit this as a justification to skip class. Second, students believe it is difficult to read in other languages, particularly English. Thridly, many students become worry about making mistake. The research was a correlation research. The population of research was students of class VIII SMPN 3 Bukittinggi, aeround Five classes, consist of 140 students. The sample for the research was 140 students selected using the total sampling technique. Tests and questionnaires were used to get the data. This research utilized the Pearson Product Moment to examine the data and tested the hypothesis. The results were consulted in a t-table with a significance level of ?=5%, and the t-test method was applied. Findings from the eighth grade PFS indicated a relationship between students' reading anxiety and comprehension. Strong correlation (0.668) was found for SMPN 3 Bukittinggi. Based on the strong correlation threshold of 0.60-0.799, the researcher determined that rxy = 0.668 with N 138 was statistically significant. It indicates that whereas ha was accepted, ho was refused. When the research's mean, ho, was rejected and ha was approved, the Pearson product moment formula was used to compare it to the R-table. The results showed that rxy (0.668) > rtable (0.167). In summary, the findings indicated a favorable relationship between eighth-grade SMPN 3 Bukittinggi students' reading comprehension and their reading anxiety.